CT-pathologic correlation in primary hepatocellular carcinoma: an implication for target delineation - Chen, Hai-yan; Ma, Xiu-mei; Ye, Ming; Hou, Yan-li; Hu, Bin; Bai, Yong-rui (Journal of radiation research, 2013)
The purpose of this investigation was to analyze the correlation between CT size and gross pathologic size for subjects with primary hepatocellular carcinoma (HCC). This analysis included 174 patients with HCC who underwent surgery. Enhanced computed tomography (CT) was performed up to 30 days before surgery. After resection, the size of the tumor on gross pathologic examination was recorded. The maximal measurement in one dimension on axial imaging and pathologic examination was extracted for statistical analysis. The clinical and pathologic sizes were compared using a percent size difference (%Δsize) as an end point. A regression analysis was applied to study the association between pathologic and radiographic size. The median radiographic and pathologic size were 70.58 ± 38.9 mm and 68.59 ± 40.56 mm, respectively. The radiographic size was larger than or equal to the pathologic size in 110/174 tumors (63.2%), and smaller in 64/174 (36.8%) tumors. Overall, the radiographic and pathologic sizes were positively correlated (r = 0.983, P = 0.000). CT seemed to overestimate the tumor size by 2.16 mm compared to final pathology (P = 0.024). The median %Δsize was 3.3%. Pathologic tumor size was significantly underestimated in patients with a tumor size 3–5 cm (P = 0.011), Grade I HCC (P = 0.023), with clear boundary (P = 0.013). We concluded that CT size and pathologic size were positively correlated, but differences did exist. Utilizing the radiographic tumor when planning radiation would have covered 63.2% of gross tumors. For a radiographic tumor size < 50 mm, utilizing a 3-mm margin around the radiographic tumor would have covered 90% of gross lesions, while a margin of 5 mm would have covered 95%, and a margin of 15 mm would have covered 100%.